The impact of Shopee's free shipping and flash sale promotions on consumers’ online shopping decisions - Handoko, Albert Jayadi; Bangsawan, Satria (Lighthouse Publishing, 2024)
This study examines the impact of Shopee's free shipping promo and flash sale promotions on consumers online shopping decisions, focusing on the society in Bandar Lampung. Online shopping has grown significantly, and promotional strategies have become crucial in attracting consumers and driving purchase behavior. Utilizing a quantitative research approach, this study collected data from Shopee users in Bandar Lampung using purposive sampling method with certain criteria to analyze the relationship between promotional offers and consumers online shopping decisions. The findings reveal that both the free shipping promo and flash sale had a positive and significantly influence consumers online shopping decisions. These promotions effectively reduce perceived costs and create a sense of urgency, encouraging shoppers to make purchases. The study highlights the importance of targeted promotional strategies such as free shipping promo and flash sale promotion in Shopee e-commerce platforms to maximize customer satisfaction.